Characterization of tissue properties in epidural needle insertion on human specimen and synthetic materials. (October 2020) - Esterer, Benjamin; Hollensteiner, Marianne; Schrempf, Andreas; Winkler, Martin; Gabauer, Stefan; Fürst, David; Merwa, Robert; Panzer, Stephanie; Püschel, Klaus; Augat, Peter
Abstract: The force experienced while inserting an 18-gauge Tuohy needle into the epidural space or dura is one of only two feedback components perceived by an anaesthesiologist to deduce the needle tip position in a patient's spine. To the best of the authors knowledge, no x-ray validated measurements of these forces are currently available to the public. A needle insertion force recording during an automated insertion of an 18-gauge Tuohy needle into human vertebral segments of four female donors was conducted. During the measurements, x-ray images were recorded simultaneously. The force peaks due to the penetration of the ligamentum supraspinale and ligamentum flavum were measured and compared to the measurements of an artificial patient phantom for a hybrid patient simulator. Based on these force peaks and the slope of the ligamentum interspinale, a mathematical model was developed. The model parameters were used to compare human specimens and artificial patient phantom haptics. The force peaks for the ligamenta supraspinale and flavum were 7.55 ± 3.63 N and 15.18 ± 5.71 N, respectively. No significant differences were found between the patient phantom and the human specimens for the force peaks and four of six physical model parameters. The patient phantom mimics the same resistive force against the insertion of an 18-gauge Tuohy needle. However, there was a highly significant (p < 0.001, effsize = 0.949 and p < 0.001, effsize = 0.896) statistical difference observed in the insertion depth where the force peaks of the ligamenta supraspinale and flavum were detected between the measurements on the human specimens and the patient phantom. Within this work, biomechanical evidence was identified for the needle insertion force into human specimens. The comparison of the measured values of the human vertebral segments and the artificial patient phantom showed promising results.